Politics of Hotspot and Uncertainties in Space and Time of the “FireD” System: A Case Study on Forest Fire and Haze Pollution in Chiang Mai 2022 - Vaddhanaphuti, Chaya (Journal of Social Sciences, Chiang Mai University, 2023)
Since 2021, Chiang Mai province has switched their wildfire and haze pollution management approach from a complete banning of open burning to authorizing burning under an optimal weather condition and allowable number of hotspots. The process is carried out under scientific consensus of the committee of “Chiang Mai's Command Centre for Wildfires and PM2.5 Prevention” through a decision support system called “FireD”. This research applies concepts of uncertainty and political geography to study the mechanism and efficiency of wildfire and haze pollution management through FireD system. From fieldwork during February to May 2022 to enquire villagers (N=11), officers (N=11) and independent researchers (N=3) in Omkoi, Mae On and Chiang Dao districts of Chiang Mai about experiences of using FireD, results show that the “FireD” system is an integrated system that is flexible for its users. The new system encourages much more systemic planning of fire management between villagers and local authorities. At the same time, however, users experienced biophysical, managerial, and technological uncertainties, as well as politics of hotspots. This resulted in disruption of the rhythm of prescribed burning and injustice toward those who whose fire is a necessity in life but lack knowledge and technological negotiating power. Moreover, uncertainties in rain and management approach disrupts. Importantly the “FireD” system has epistemological and practical limitation in solving wildfire and haze problem that are in themselves transboundary issue since its authority can only be implemented within the territory of Chiang Mai province.